1997
DOI: 10.1046/j.1365-2710.1997.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of quality of life, compliance, clinical outcomes and life satisfaction: a cross-sectional study on hypertensive geriatrics

Abstract: INTRODUCTION Objective: (i) To assess quality of life (QoL) profilesIn 1990, geriatrics (aged 65 years and above) accounted in hypertensive geriatrics with SF-36; (ii) to assess for only 1 in every 25 Americans (3·1 million). By 1994 the compliance of geriatrics to medications; (iii) to this figure had risen to 1 in 8 Americans (33·2 million). estimate clinical outcomes (reduction in systolic andIt is projected that there will be 80 million (apdiastolic blood pressure); (iv) to assess life satisproximately 1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…This finding is also important, as the literature describing the relationship between adherence and HRQL appears to be rather limited. One published study (Pippalla, Chinburapa, Duval, & Akula, ) failed to show any associations between the variables in question, a second study found weak associations (Cote, Farris, & Feeny, ), and a third study identified associations between two items in an HRQL measure and adherence (Sung et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also important, as the literature describing the relationship between adherence and HRQL appears to be rather limited. One published study (Pippalla, Chinburapa, Duval, & Akula, ) failed to show any associations between the variables in question, a second study found weak associations (Cote, Farris, & Feeny, ), and a third study identified associations between two items in an HRQL measure and adherence (Sung et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessing the relationship between QoL perception and medication adherence have produced different results, which may be due to variation in the techniques used to measure QoL and the study populations examined. [53][54][55] Further research is needed to understand the mechanisms that affect adherence to antihypertensive medications.…”
Section: Factors Associated With Nonadherencementioning
confidence: 99%
“…Results from prior studies examining the relationship between health-related quality of life (HRQOL) and antihypertensive medication adherence have been conflicting [5,10,11]. This may be due to variation in both the techniques used to measure HRQOL and the study populations examined [12].…”
Section: Introductionmentioning
confidence: 99%